2014
DOI: 10.1007/s10620-014-3360-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Colitis with NovaSil Clay Therapy

Abstract: NovaSil mitigated the effects of TNBS-induced colitis based on reduction in systemic markers of inflammation, significant improvement in weight gain, and intestinal microbial profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…Although the mechanism of action of smectite is not clearly understood, it is an activated natural aluminosilicate clay that can adsorb water and presents multiple other interesting properties: it prevents toxins, bacteria and viruses adhering to intestinal membranes, 9,13‐17 it has been shown to strengthen the mucosal barrier in vitro and in vivo, 18‐20 to have some anti‐inflammatory properties, 17,18,21,22 to decrease intestinal bacterial translocation 23 and to stabilize the intestinal microbiome 16,17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism of action of smectite is not clearly understood, it is an activated natural aluminosilicate clay that can adsorb water and presents multiple other interesting properties: it prevents toxins, bacteria and viruses adhering to intestinal membranes, 9,13‐17 it has been shown to strengthen the mucosal barrier in vitro and in vivo, 18‐20 to have some anti‐inflammatory properties, 17,18,21,22 to decrease intestinal bacterial translocation 23 and to stabilize the intestinal microbiome 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…Its role in the treatment of acute diarrhoea in children and adults is well established, 24,25 and a beneficial effect has been found in different types of diarrhoea and different species 21,22,26‐28 . In a case series of 17 dogs with intractable CID, 10 dogs (58.8%) had resolution of their diarrhoea after 48 to 72 hours of treatment, and improvement was noted in the remainder 29…”
Section: Introductionmentioning
confidence: 99%
“…Smectite has been effectively used in the treatment of several gastrointestinal diseases, including infectious diarrhea and food allergy (37). In experimental colitis models was found that administration of smectite associated with absorption of inflammatory proteins, reduction in systemic markers of inflammation (IL-2, IL-6, IL-8 and IL-12, TNFa, IFNg) (38)(39)(40) and significant improvement in intestinal microbial profile (41). The Dening et al proposed that spray dried smectite clay particles may be developed as novel antiobesity treatments (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, montmorillonite (bentonite) clay adsorbs uric acid and promotes the diffusion of uric acid from blood vessels to intestine, prevents absorption of uric acid in intestine and decreases SUA [141]. In mice with induced colitis, the processed calcium montmorillonite clay product, Novasil, reduced systemic markers of inflammation, and improved both weight gain and the intestinal microbial profile [142]. Aflatoxin levels in the serum and the urine of adults have been reported to decrease following the consumption of Novasil [143], indicating that the clay is acting as an adsorbent in vivo.…”
Section: Increasing Intestinal Uric Acid Excretionmentioning
confidence: 99%